Analysis of Job Characteristics, Performance, and Work Life Balance in Generation Z Workers - Rensiana, Septa; Wulandari, Jeni; Roni, May (Indonesian Journal of Economics and Management, 2024)
Generation Z employees generally prioritize flexibility in their work and an environment that promotes personal growth. This learn focus to search the affect of job characteristics on the performance of Generation Z workers in Bandar Lampung, with work-life balance serving as a moderating variable. A quantitative approach was employed, using the PLS-SEM method, with data collected from 100 informant through purposive sampling and analyzed via SmartPLS 3.0. The analysis included outer model tests, inner model tests, and direct and indirect affect hypothesis testing. The findings reveal that job characteristics have a positive and significant effect on both work-life balance and performance, while work-life balance has a significant negative impact on performance. However, work-life balance does not significantly moderate the affect of job characteristics to performance, indicating that it weakens the relationship. These insights are intended to inform managerial strategies regarding work-life balance policies to enhance the performance of Generation Z workers.